Tracing the Impact of Coastal Water Geochemistry on the Re‐Os Systematics of Macroalgae: Insights From the Basaltic Terrain of Iceland. Issue 9 (13th September 2018) - Sproson, Adam D.; Selby, David; Gannoun, Abdelmouchine; Burton, Kevin W.; Dellinger, Mathieu; Lloyd, Jeremy M.
Abstract: This study presents rhenium (Re) and osmium (Os) elemental and isotope data for macroalgae, dissolved load, and bed load from Icelandic coastal and/or river waters, an environment adjacent to predominantly basaltic terrains, ranging in age from historic to ~12 Ma. Both the Re (0.1 to 88.4 ppb) and Os (3.3 to 254.5 ppt) abundance in macroalgae are shown to be primarily controlled by uptake from the dissolved load of local seawater and are largely dependent on the relative influence of local freshwater inputs. Incorporation of Re and Os into macroalgae appears to be complicated by additional Re and Os uptake from the bed load. The 187 Os/ 188 Os (0.16 to 0.99) composition of macroalgae is highly variable and is explained in terms of an unradiogenic 187 Os/ 188 Os contribution from rivers draining younger basaltic catchments that have undergone congruent weathering (and/or hydrothermal input) and a radiogenic 187 Os/ 188 Os contribution from two distinct sources: rivers draining older catchments that have undergone incongruent weathering of radiogenic primary basaltic minerals and North Atlantic seawater. The 187 Re/ 188 Os composition (~65 to 40, 320) of macroalgae traces that of water, with higher values associated with higher salinity waters, but far exceeds the 187 Re/ 188 Os of water due to the preferential uptake of Re over Os by macroalgae in areas of high dissolved and/or bed load Re abundances. This study substantiates the utility of macroalgae as a proxy for the long‐term (months to years) average 187 Os/ 188 Os composition of seawater, which holds the potential to elucidate a range of Earth system and anthropogenic processes. Key Points: This article contains Re‐Os abundance and isotope data for macroalgae from Icelandic coastal waters Isotope data reflect changes in basaltic weathering and estuarine or coastal mixing This article provides a novel approach to trace a range of Earth system and anthropogenic processes